The Future We Get Might Not Be the Future We Want: Analyzing the Rio+20 Outcomes. Issue 3 (16th July 2013) - Pattberg, Philipp; Mert, Ayşem
Abstract The Rio+20 Summit resulted in a policy outcome that, according to most observers, did not meet the requirements for a deep transformation of the current unsustainable practices that contribute to global environmental change. In light of this assessment, scholars and practitioners have questioned the effectiveness of intergovernmental conferences to solve environmental problems and suggested alternatives, including voluntary commitments, public–private partnerships and bottom‐up approaches. This survey article analyzes the Rio+20 outcomes and argues that, while the overtly high expectations of the public, media, NGOs and scientists have not been met, the concrete results might include the seeds for a substantive transformation of current unsustainable practices. In this context, this article also urges leaders not to abandon international agreements for governing global change prematurely.